A case study on technology-based start-ups in the Philippines - Dee, Robert Isaac T. (University of the Philippines Diliman, 2015)
This paper aims to study how start-up companies operate and start. The paper also aims to identify the challenges these start-ups faced before they become successful. The paper will analyze a number of start-up companies and make a comparative analysis out of their experiences and draw conclusions and recommendations from it. With all the gathered information, the proponent hopes to offer some advice to aspiring entrepreneurs so that they will have a better chance at survival. The success of this study lies on the availability of public information.